Incidence, prevalence and survival in patients with Langerhans cell histiocytosis: A national registry study from England, 2013–2019. (19th September 2022) - Liu, Hanhua; Stiller, Charles A.; Crooks, Colin J.; Rous, Brian; Bythell, Mary; Broggio, John; Rankin, Judith; Nanduri, Vasanta; Lanyon, Peter; Card, Tim R.; Ban, Lu; Elliss‐Brookes, Lucy; et al.
Summary: This analysis is the largest population‐based study to date to provide contemporary and comprehensive epidemiological estimates of all third edition of the International Classification of Diseases for Oncology (ICD‐O‐3) coded Langerhans cell histiocytosis (LCH) from England. People of all ages were identified from the National Cancer Registration Dataset using ICD‐O‐3 morphologies 9751–9754 for neoplasms diagnosed in 2013–2019. A total of 658 patients were identified, of whom 324 (49%) were children aged <15 years. The age‐standardised incidence rate was 4.46 (95% confidence interval [CI] 3.99–4.98) per million children and 1.06 (95% CI 0.94–1.18) per million adults aged ≥15 years. Prevalence of LCH was 9.95 (95% CI 9.14–10.81) per million persons at the end of 2019. The 1‐year overall survival (OS) was 99% (95% CI 97%–100%) for children and 90% (95% CI 87%–93%) for adults. Those aged ≥60 years had poorer OS than those aged <15 years (hazard ratio [HR] 22.12, 95% CI 7.10–68.94; p  < 0.001). People in deprived areas had lower OS than those in the least deprived areas (HR 5.36, 95% CI 1.16–24.87; p  = 0.03). There will inevitably be other environmental factors and associations yet to be identified, and the continued standardised data collection will allow further evaluation of data over time. This will be increasingly important with developments in LCH management following the large collaborative international trials such as LCH IV.